Crisis of Faith Amid Hoax Phenomenon in Indonesia; Perspective Critical Analysis by Charles S. Peirce - Eka Safitri; Amin Abdullah (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2024)
The phenomenon of hoaxes is becoming more and more widespread in the digital age and it is difficult to stop. Hoax is a disease as terrifying as the symptoms of rampant corruption and narcotics. The problem of hoaxes cannot be ignored because the more massively these hoaxes can undermine the morale of the nation, the more it can even lead to a crisis of faith. Belief in the knowledge gained is a human need, but the presence of false reports will eventually lead to a crisis of faith. The purpose of this article is to analyze a hoax phenomenon that still pervades the digital world, using Charles S. Peirce's analytical meter on the theory of truth. The crisis of faith must be overcome so that it does not last too long and cause information chaos in society. This research is an analytical-descriptive study using data sources from digital media, online sites, books, magazines, news. Data was analyzed using Charles S. Peirce's theory of truth. From the analysis carried out, the conclusion is that obtaining basic beliefs requires a scientific method through a scientific attitude in collecting information. When people receive information from any source, true faith must first go through a period of doubt and think critically about the knowledge gained. The information received is processed in the mind based on the scientific method process followed by a person to acquire essential beliefs.